2018
DOI: 10.11152/mu-1548
|View full text |Cite
|
Sign up to set email alerts
|

Good performance of liver stiffness measurement in the prediction of postoperative hepatic decompensation in patients with cirrhosis complicated with hepatocellular carcinoma

Abstract: LSM has a similar performance to HVPG in predicting decompensation at 3 months in patients with early HCC submitted to liver resection. Three-month decompensation is better associated with survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Finally, LSM by VCTE predicts not only the presence of CSPH but also CSPH-related complications such as hepatic decompensation in patients with compensated cirrhosis due to chronic hepatitis C (CHC), 31 in (mostly) cirrhotic patients of diverse etiologies, 32,33 as well as in patients undergoing hepatectomy, [34][35][36] with similar accuracy, as compared with HVPG. However, all of these studies were rather small, limiting the statistical power to detect clinically meaningful differences in the prognostic value of LSM by VCTE and HVPG.…”
Section: Liver Stiffness Measurement By Vibration-controlled Transienmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, LSM by VCTE predicts not only the presence of CSPH but also CSPH-related complications such as hepatic decompensation in patients with compensated cirrhosis due to chronic hepatitis C (CHC), 31 in (mostly) cirrhotic patients of diverse etiologies, 32,33 as well as in patients undergoing hepatectomy, [34][35][36] with similar accuracy, as compared with HVPG. However, all of these studies were rather small, limiting the statistical power to detect clinically meaningful differences in the prognostic value of LSM by VCTE and HVPG.…”
Section: Liver Stiffness Measurement By Vibration-controlled Transienmentioning
confidence: 99%
“…104 Llop et al 100 confirmed the applicability of previously established highly sensitive (13.6 kPa 25 ) and highly specific (21 kPa 28 ) LSM by VCTE cut-offs for ruling-in and ruling-out CSPH in patients with HCC. Besides diagnosing CSPH, several noninvasive methods (e.g., LSM [34][35][36]45,46 and SSM, 54,55 ICG clearance, 75 and VWF 96 ) have been shown to directly predict adverse outcomes (i.e., liver failure, hepatic decompensation, and/or late recurrence) after hepatectomy; however, most of these studies also included non-ACLD patients, who are more easy to classify as compared with patients with compensated cirrhosis and CTP stage A.…”
Section: Ruling-in and Ruling-out/diagnosing Clinically Significant Pmentioning
confidence: 99%
“…Liver stiffness (LS) assessed by TE or shear-wave-elastography has been reported as a significant predictor of PHLF in HCC patients. [12][13][14] Magnetic resonance elastography (MRE), an magnetic resonance imaging (MRI)-based tool for the quantitative assessment of LS, is considered the most accurate non-invasive technique for assessing liver fibrosis. 15,16 Recently, MRE-assessed LS (MRE-LS) has been highlighted as a potential prognostic biomarker in HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Liver stiffness measurement In the last few years, the liver stiffness measurement (LSM) has been proposed as a practical and widely validated surrogate of liver fibrosis and portal hypertension, able to accurately predict the risk of cirrhosis [79] , CSPH [80] and its complications, such as the development of varices [81] and hepatic decompensation [82] . Given that these attributes are major determinants of the risk of PHLF development, LSM has been investigated as a predictor of decompensation and other complications after hepatic resection with several methods that are mainly ultrasound-based [11,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] [ Table 3].…”
Section: Ultrasound-based and Other Imaging Predictorsmentioning
confidence: 99%